Lupi e leoni medici (dal corpus esopico al «Fabulario» di Mey) (Carte Romanze, 2019)
The trajectory of the Aesopic fable «The Wolf as Physician» goes through a series of transformations that have an ideological connotation. During the Middle Ages, the defense of cunning as a survival weapon (Aesop, Babrius, Aphthonius) acquires political overtones, in the context of feudal hierarchy and the struggles against monarchical power (Romulus, Gualterus Anglicus, Archpriest of Hita). On the other hand, the contamination with Babrius’ fable «The mule» emphasizes the problem of the lineage (Disciplina clericalis, Clemente Sánchez, Baldus), leading to a criticism of fatuous knowledge (Novellino, Isopete, Mey).